2012
DOI: 10.1136/acupmed-2011-010118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Intervention and Postoperative Pain on Electrical Skin Resistance at Acupuncture Points: An Exploratory Study

Abstract: Objectives One theory about acupuncture suggests that pathological processes can cause measurable changes in electrical skin resistance (ESR) at acupuncture points (APs). Although the theory has yet to be proven, ESR measurements (ESRMs) form a frequently used part of contemporary acupuncture. The aim of this study was to test the so-called 'electrical responsiveness' of APs in the setting of a defi ned operative trauma. Methods ESRMs (n=424) were performed at the APs and surrounding skin of GB34 and ST38 in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In addition, the acupoints with high conductance in IMH rats but not naïve rats showed higher neurogenic inflammation and plasma extravasation than those of naïve rats (Figures 3G,H). Our hypothesis is further supported by another study showing that more significant changes in skin impedance at acupoint GB34 were observed in patients that had undergone surgery than in healthy subjects (Kramer et al, 2012). Importantly, previous studies point out that the precision of skin conductance measurements can be influenced by numerous factors such as skin dryness, skin thickness, size of the sensing electrode, pressure applied on the electrode, interelectrode distance, room temperature, and humidity (Ahn and Martinsen, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the acupoints with high conductance in IMH rats but not naïve rats showed higher neurogenic inflammation and plasma extravasation than those of naïve rats (Figures 3G,H). Our hypothesis is further supported by another study showing that more significant changes in skin impedance at acupoint GB34 were observed in patients that had undergone surgery than in healthy subjects (Kramer et al, 2012). Importantly, previous studies point out that the precision of skin conductance measurements can be influenced by numerous factors such as skin dryness, skin thickness, size of the sensing electrode, pressure applied on the electrode, interelectrode distance, room temperature, and humidity (Ahn and Martinsen, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown that physical and psychological conditions alter the electrical impedance of APs. 22 If acupuncture alters the electrical impedance of APs and meridians, it is possible that the affect of acupuncture on improving medical conditions can be explained by this theory.…”
Section: Introductionmentioning
confidence: 99%